ROLE OF PUBLIC SECTOR BANKS IN ENHANCING FINANCIAL LITERACY AND EMPOWERMENT OF WOMEN ENTREPRENEURS IN THIRUVANANTHAPURAM DISTRICT - Chinchu V U; Rangith, M Josephin (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Women entrepreneurs are pivotal to economic growth, contributing to income generation, employment creation, and social transformation. In Kerala, especially Thiruvananthapuram District, women increasingly engage in small and medium enterprises, self-help groups, and service-oriented businesses. Despite their growing presence, they face challenges such as limited access to financial resources, low awareness of institutional credit facilities, and inadequate knowledge of financial management. Public Sector Banks (PSBs) play a critical role in addressing these challenges by offering credit facilities, promoting savings, implementing government schemes, and conducting financial literacy programs. This study examines the role of PSBs in enhancing financial literacy and empowering women entrepreneurs in Thiruvananthapuram. Using a descriptive and analytical research design, primary data was collected from 140 women entrepreneurs through structured questionnaires, complemented by secondary sources. Analysis revealed that awareness and utilization of schemes like MUDRA loans, SHG–Bank Linkage Programme, and digital banking services are high, while specialized loans and training programs are underutilized. Education, income, and type of business significantly influence financial literacy and empowerment, whereas age and marital status do not. Correlation and regression analyses confirmed a strong positive relationship between financial literacy and economic, social, and psychological empowerment. The study concludes that PSBs significantly contribute to holistic empowerment, but targeted interventions are needed to enhance utilization of specialized schemes and training programs for inclusive growth.